Predicting the transition to chronic pain six months after an ED visit for acute pain. A prospective cohort study - Friedman, Benjamin W. (J Emerg Med, 2020)
BACKGROUND. Acute pain may transition to chronic pain, a potentially debilitating illness. OBJECTIVES. We determined how often acute pain transitions to chronic pain among ED patients and whether persistent pain 1 week after the ED visit was associated with chronic pain. METHODS. An observational cohort study conducted in two EDs. We included adults with acute pain (≤10 days) if an oral opioid was prescribed. Exclusion criteria were recent opioid use or use of any analgesics regularly prior to onset of the pain. Research associates interviewed patients during the ED visit, and 1 week and 6 months later. The primary outcome, chronic pain, was defined as pain on >50% of days since ED discharge. We constructed logistic regression models to evaluate the association between persistent pain 1 week after an ED visit and chronic pain while adjusting for demographic and treatment variables. RESULTS. During a 9-month period, we approached 733 patients for participation and enrolled 484. 450/484(93%) provided one week outcome data and 410/484(85%) provided six month outcome data. One week after the ED visit, 348/453(77%, 95%CI:73, 80%) patients reported pain in the affected area. New onset chronic pain at six months was reported by 110/408 (27%, 95%CI: 23, 31%) patients. Presence of pain one week after ED visit was associated with chronic pain (OR3.6, 95%CI:1.6,8.5). CONCLUSIONS. About one-quarter of ED patients with acute pain transition to chronic pain within six months. Persistence of pain one week after the ED visit can identify patients at risk of transition.